DIFUSI INOVASI KESENIAN DRUMBLEK (Studi Kasus Kelompok Drumblek B’CAD Desa Bener, Kec. Tengaran, Kab. Semarang) - Negara, Doni Kusuma; Muliana, I Nengah (Institut Seni Indonesia (ISI) Surakarta, 2022)
This study describes the diffusion and adoption of the drumblek art in the people of Bener Village, Tengaran District, Semarang Regency, Central Java. This research uses interview, observation, and literature study methods. The theory of innovation diffusion by Everett Rogers is used to analyze the process and stages of the diffusion and innovation of drumblek art in the Bener community. This research shows that the art of drumblek through the formation of the B’CAD group as a forum to unite and resolve disputes that previously occurred between the residents of Bener Village. The process of diffusion of drumblek art innovations in Bener Village is a stage of the process of knowledge, persuasion, decision making, implementation and confirmation, after going through these stages a B’CAD group is then formed with all the consequences that result in it.